Block-based Tchebichef image watermarking scheme using psychovisual threshold - Ernawan, Ferda; M. Nomani, Kabir; Mohamad Fadli, Zolkipli; Zuriani, Mustaffa (IEEE, 2017)
Digital multimedia has drastically increased the production and distribution of digital data in the recent years. Unauthorized manipulation and ownership of digital image have become a serious issue. In this paper, we propose a watermarking scheme which uses block-based Tchebichef moments considering psychovisual threshold. The psychovisual threshold is used to prescribe the potential location of embedded watermark. The proposed watermarking scheme considers minimum modified entropy values to determine the embedded blocks. The lowest psychovisual error threshold on each selected block are chosen as the best location to insert the watermark image. Experimental results demonstrate that the embedding watermark into the lowest Tchebichef psychovisual threshold can produce a good level of imperceptibility. The watermark recovery is strongly robust against JPEG compression.